Transparansi Pelaporan Dana Kampanye Dalam Mewujudkan Pemilu Yang Berintegritas - Nailina Paramita Neina; Aidul Fitriciada Azhari; Nuria Siswi Enggarani (Jurnal Jurisprudence, 2021)
ABSTRACTObjective: This study aims to describe the transparency of the 2019 election campaign funds based on the laws and regulations and to find out in depth the legal consequences and sanctions received by election participants in reporting campaign funds.Methodology : The type of research used is empirical juridical, namely, examining everything related to legal provisions, as they have been implemented and how they were implemented in the broader community. The research sites are at the General Election Commission (Komisi Pemilihan Umum) office of Blora Regency, the Office of the Election Supervisory Board, and the Liaison Officer of the participating political parties. In this study, the solution to the problem lies in the transparency of reporting campaign funds for 2019 election participants, which researchers emphasize on the election participants for candidates for members of the Regional People's Representative Council of Blora Regency.Results : Transparency in Law Number 7 of 2017 concerning General Elections and General Election Commission Regulation Number 24 of 2018 as amended by General Election Commission Regulation Number 34 of 2018 concerning General Election Campaign Funds and Implementation of Campaign Fund Reporting for Election Contestants to Realize The 2019 election had been held at the Blora Regency General Election Commission. The General Election Commission of Blora Regency had implemented transparency in campaign finance reports in the 2019 Election. This can be seen from the regulations governing the Blora Regency General Election Commission's strategy in applying the principle of transparency regarding campaign finance reports in the 2019 Election in Blora Regency.Applications of this study: This study is expected to produce a formulation on campaign finance reporting that will be used by the General Elections Commission to develop policies and regulations on campaign finance reporting..  Novelty/ Originality of this study: Election results have had a significant impact on Indonesia's democratic order from year to year. If a regulation is properly implemented, it will have an impact on the general election process's pattern of continuity. The goal of this study was to talk about campaign finance transparency in the 2019 elections in Blora Regency..